OCCUPATIONAL HEALTH AND SAFETY IMPACTS, ENVIRONMENTAL CONDITIONS, AND JOB PLEASURE ON EMPLOYEE PERFORMANCE AT CV SURYA ANANTA SENTOSA MUNCAR BANYUWANGI - Anggraini, Sabella; Bayu Wijayantini; Septy Holisa Umami (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to determine and analyze Occupational Health and Safety (K3), Work Environment, and Job Satisfaction towards Employee Performance at CV Surya Ananta Sentosa Muncar Banyuwangi. Method: This study uses a quantitative method. Research-related information, namely primary information obtained through observation, distributing questionnaires, interviews, and using secondary data through documentation. The research sample consists of 40 employees at CV Surya Ananta Sentosa in Muncar Banyuwangi. For data analysis, the author used Line Development Testing Increase. Results: The results of hypothesis testing state that OHS does not have a significant impact on employee performance, working conditions have a significant impact on employee performance, and working success does not have a significant impact on employee performance. Novelty: This study is based on the problems that occur at CV Surya Ananta Sentosa, namely the lack of attention to occupational safety and health. Although the company has provided protective equipment such as masks, gloves, and boots to prevent work accidents in the distribution section, employees often neglect to use them due to a lack of awareness and the perception that accidents are rare coincidences.